Kongeriket Polens gjenreisning eller "densy vend edeling"? Manifestet av 5. november 1916 i norsk presse - Stachurska, Marta (Folia Scandinavica Posnaniensia, 2007)
The Declaration of 5th November was seen as one of the most significant international events in the autumm of 1916. European newspapers, not least the Norwegian ones, printed the news from Poland on the front pages. The reason for such a switch in the interest of the inter-national public opinion was the Allies’ concern that the Central Powers wanted to strengthen their armies with Polish recruits. Until that time the Norwegian coverage of the Polish question had been strongly influenced by the German news agencies, which usually were the main sources of information about developments in the Polish regions. The events of November 1916 changed this tendency by prompting the Norwegian newspapers to print the relevant comments on the Polish question from the western Allies and Russia. This novel approach, however, was not entirely devoid of subjectivity, as might have been seen in the article “Poland’s seventh partition” published in the Aftenposten of 15th November, 1916, in which Russia, though at that time in actual control of the occupied territories of Poland, was presented as a brotherly defender of the Polish nation.